Biogas desulfurization by photosynthetic process with microalgae and absorption by washing with water (Research, Society and Development, 2022)
Biogas has high potential to be used in the generation of electricity and heat and as a replacement for vehicular fuel, favoring the reduction of dependence on fossil fuels. In order for biogas to be used safely and effectively, H2S needs to be removed at levels tolerated for its intended purpose. The objective of this work was to evaluate the potential of a pilot scale scrubber to promote biogas desulfurization using the photosynthetic process with microalgae and the absorption process by washing with water at atmospheric pressure. The crude biogas presented H2S concentration above 1.000 ppm, by gas chromatography analysis. For the photosynthetic system with microalgae, the concentration of H2S in the purified biogas was reduced to 11 ppm with 30 minutes of operation and at 180 minutes it was completely removed, remaining so until the end of the daily cycle of system operation. For the water washing system, despite the concentration of hydrogen sulphide in the purified biogas having decreased considerably in the studied interval, an increase in the content was noticed over time, with readings ranging from 37,8 ppm to 188,4 ppm, indicating that there may be total saturation of this component, if the system works uninterruptedly. Thus, the removal of hydrogen sulphide through the biological process with microalgae was successfully performed in a pilot scale purifier, and its performance was classified as promising, providing appropriate conditions for desulfurization of biogas.